Additional diagnostic value of electron microscopic examination in endomyocardial biopsy in patients with suspected non-ischemic cardiomyopathy. Issue 2 (February 2023) - Yamamoto, Masayoshi; Sato, Kimi; Murakoshi, Nobuyuki; Yamada, Yu; Nakagawa, Daishi; Nakatsukasa, Tomofumi; Ishizu, Tomoko; Ieda, Masaki
Abstract: Background: Electron microscopy enables a finely detailed analysis of ultra-structural features, and hence, it generally has an added diagnostic value to light microscopy alone. However, no studies have verified the additional diagnostic value of electron microscopic examination in patients with suspected non-ischemic cardiomyopathy. Methods: A total of 294 consecutive patients with non-ischemic cardiomyopathy who underwent endomyocardial biopsy were prospectively enrolled. Patients were divided into three groups according to left ventricular morphology assessed using echocardiography. Myocardial specimens were collected from the right ventricular septum and examined by light microscopy. Electron microscopy was performed subsequently to evaluate the additional diagnostic value. Results: Altogether, 294 patients were analyzed, including 160 (55 %), 96 (33 %), and 35 (12 %) patients who were diagnosed with primary, secondary, and unclassified cardiomyopathy, respectively. In patients with dilated cardiomyopathy-like morphology, the detection rate of disease-specific histological findings was relatively low compared to that in patients with other cardiac morphologies. The additional diagnostic value of electron microscopy was observed in eight patients, including five with Fabry disease, one with cardiac amyloidosis, one with mitochondrial cardiomyopathy, and one with triglyceride deposit cardiomyovasculopathy. Among the 18 cardiac amyloidosis cases, electron microscopy detected amyloid fibrils in all patients, whereas light microscopy could not detect amyloid deposition in 1 patient. Among one of five patients with Fabry disease, light microscopy did not show obvious vacuolated cardiomyocytes, but zebra bodies were detected by electron microscopy, leading to the diagnosis of cardiac Fabry disease. The diagnostic value of electron microscopic examination in patients with cardiac sarcoidosis was not observed. Conclusions: The additional diagnostic value of electron microscopy was observed in patients with secondary cardiomyopathy, in whom light microscopy did not show disease-specific histological findings. Electron microscopy should be performed in cases where secondary cardiomyopathy is strongly suspected with no disease-specific findings by light microscopy. Graphical abstract: Unlabelled Image Highlights: The diagnostic value of electron microscopic examination in endomyocardial biopsy Detection rate of specific histological findings according to cardiac morphology Electron microscopic examination in Fabry disease and cardiac amyloidosis